Similarity of wh-Phrases and Acceptability Variation in wh-Islands - Atkinson, Emily; Apple, Aaron; Rawlins, Kyle; Omaki, Akira (Frontiers in Psychology, 2016)
In wh-questions that form a syntactic dependency between the fronted wh-phrase and its thematic position, acceptability is severely degraded when the dependency crosses another wh-phrase. It is well known that the acceptability degradation in wh-island violation ameliorates in certain contexts, but the source of this variation remains poorly understood. In the syntax literature, an influential theory – Featural Relativized Minimality – has argued that the wh-island effect is modulated exclusively by the distinctness of morpho-syntactic features in the two wh-phrases, but psycholinguistic theories of memory encoding and retrieval mechanisms predict that semantic properties of wh-phrases should also contribute to wh-island amelioration. We report four acceptability judgment experiments that systematically investigate the role of morpho-syntactic and semantic features in wh-island violations. The results indicate that the distribution of wh-island amelioration is best explained by an account that incorporates the distinctness of morpho-syntactic features as well as the semantic denotation of the wh-phrases. We argue that an integration of syntactic theories and perspectives from psycholinguistics can enrich our understanding of acceptability variation in wh-dependencies.